PHYTOREMEDIATION OF ACENAPHTHENE (ACN), NAPHTHALENE (NAP) AND PHENANTHRENE (PHE) CONTAMINATED SOIL USING Gardenia Jasminoides PLANT (FUDMA JOURNAL OF SCIENCES, 2023)
In this study, greenhouse pots experiment was conducted to determine the phytoremediation potential of the Gardenia jasminoides plant. The plant was transplanted into 4.0 kg soil spiked with three different concentrations of the polycyclic aromatic hydrocarbons (PAHs); 1600 mg Acenaphthene (ACN), 2000 mg naphthalene (NAP) and 2400 mg phenanthrene (PHE) respectively. The Plant was allowed to grow under greenhouse conditions in triplicates with sufficient watering for ten weeks in pots containing soil contaminated with the three PAHs and control. At the end of the experiment, the levels of PAHs in the extracts of soil, roots and shoots were analyzed using high performance liquid chromatography system from Shimadzu equipped with a UV-VIS detector (SPD-20-AV). The results showed that, bioconcentration factor (BCF) values in control Experiment are 0.74 for ACN, 0.57 and 1.64 for NAP which is greater than one. Translocation factors (TF) values in control experiment are 1.23 for ACN, 1.0 for PHE and 1.20 for NAP. BCF values are greater than one at all the three different spiked experiment, 8.66 for ACN, 2.30 for PHE and 4.31 for NAP. The results also showed that the Plant was able to remove NAP with TF=2.32, ACN with TF=2.94 and PHE with TF=3.62 from contaminated soils. High values of one and above for the BCF and TF indicates high accumulation of the PAHs in the shoots of the plant. The plant may therefore be best described as phytoextractor of naphthalene, acenaphthene and phenanthrene in the soil.
Keywords: Gardenia Jasminoides; Polycyclic Aromatic Hydrocarbons; Accumulation; Soil